Serological survey of measles immunity in the Czech Republic, 2013 - Tomášková, Hana; Zelená, Hana; Kloudová, Alena; Tomášek, Ivan (Central European Journal of Public Health, 2018)
OBJECTIVES: The aim of the serological survey of measles was to obtain information on the prevalence of antibodies against measles and to verify the effectiveness of vaccination in the Czech population in order to protect public health. METHODS: The serological survey was carried out in the Czech Republic in 2013. Antibodies against measles were tested in 3,111 serum samples of participants aged 1-64 years. Serum samples were tested for the presence of immunoglobulin G (IgG) antibodies by enzyme immunoassay (EIA). The vaccination status assessment was based on the medical documentation. Seroprevalence differences were evaluated by sex and age using the Pearson's χ2 test at 5% significance level. RESULTS: The overall seroprevalence reached 93.0% (2,893/3,111) (95% CI 92.0-93.9). No statistically significant difference was found between men and women (p=0.724). A lower seroprevalence was identified in the first age group (1-year old children) 62% (62/100), as the vaccination has not yet been completed in this age group. The second lowest seroprevalence 80.4% (160/199) was identified in the age group of 35-44 years. The highest seroprevalence 97.7% (387/396) (95% CI 95.7-99.0) was in the population with naturally-induced immunity (age above 45 years). In the individuals with two doses seroprevalence reached 94.1% (2,081/2,212) (95% CI 93.0-95.0). The level of IgG antibodies decreased in persons above 7 years of age. CONCLUSIONS: Based on the results of the serological survey carried out in 2013 in the Czech Republic, it has been decided to postpone the second MMR (measles, mumps and rubella) dose to the age of 5-6 years.
Keywords: Seroepidemiologic Studies; mužské pohlaví; protilátky virové; Male; Czech Republic; Antibodies, Viral; Female; Humans; vakcína proti spalničkám, příušnicím a zarděnkám; kojenec; Measles; lidé; Middle Aged; ženské pohlaví; lidé středního věku; spalničky; Infant; Česká republika; mladiství; Immunization Schedule; Prevalence; očkovací schéma; Child; dítě; Adolescent; séroepidemiologické studie; Child, Preschool; dospělí; Measles-Mumps-Rubella Vaccine; Adult; předškolní dítě; prevalence